Mexican Fruit Fly, Anastrepha ludens (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems; John B. Heppner; Gary J. Steck; Thomas R. Fasulo; James L. Nation (EDIS)
The Mexican fruit fly is a very serious pest of various fruits, particularly citrus and mango, in Mexico and Central America. Its natural distribution includes the Rio Grande Valley of Texas, where populations routinely attain pest status if control measures are not practiced. It is a frequent invader in southern California and Arizona. Mexican fruit fly represents a particular threat to Florida because of its special affinity for grapefruit, of which Florida is one of the world's leading producers. Mexican fruit fly larvae are transported widely in infested fruits. This revised 6-page fact sheet was written by H. V. Weems, Jr, J. B. Heppner, G. J. Steck, T. R. Fasulo, and J. L. Nation, and published by the UF Department of Entomology and Nematology, January 2012.